Kesiapsiagaan Masyarakat dalam Menghadapi Bencana Banjir di Desa Bulurejo, Kecamatan Nguntoronadi, Kabupaten Wonogiri: Community Preparedness in Facing Flood Disaster in Bulurejo Village, Nguntoronadi Subdistrict, Wonogiri Regency - Mayiswa Fatika Sari, Mayiswa Fatika Sari; Andi Irwan Benardi, Andi Irwan Benardi; Erni Suharini, Erni Suharini; Vina Nurul Husna, Vina Nurul Husna (Universitas Negeri Semarang, 2025)
Floods are the most dominant disaster in Indonesia. Community preparedness is essential for effective planning and response to flood disasters, especially in flood-prone areas such as Bulurejo Village, Nguntoronadi District, Wonogiri Regency. The study aims to determine the level of community preparedness and the factors associated with preparedness for flood disasters in Bulurejo Village. This research uses a mixed-method approach, with the population consisting of all household heads in flood-affected neighborhoods using proportional random sampling. Data collection by observation, interviews, documentation, and questionnaires. Data analysis by descriptive percentages and Chi-Square correlation tests. The study results showed that the community preparedness level in Bulurejo Village scored an index of 72, categorized as